USING PICTURE SERIES TO IMPROVE STUDENTS’ PARTICIPATION IN LEARNING WRITING RECOUNT TEXT - Darma, Angga Aditiya; Ikhsanudin, Ikhsanudin; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was conducted to improve the students? participation in learning writing recount text by using picture series. Most of the students did not actively participate in the class, when the teacher taught, they did not pay attention to the teacher, they talked to each other and did not participate in completing the assigned task. To achieve the research purpose, a classroom action research was conducted. This research was implemented to 33 eighth grade class D students. The research was done in three cycles. The writer observed the improvement of students? participation by collecting the data through observation technique. The result of data analysis showed that the students? participation improved during the process of teaching and learning writing recount text using picture series. The students could active participate in the teaching learning process. It showed that the percentage of students? participation improved from 43% (cycle 1) to 45% (cycle 2) increased to 72% (cycle 3). It can be concluded that the students? participation in learning writing recount text improved using picture series. Thus, it is recommended to the teachers to use picture series as a media to improve students? participation. Keywords: Learning Writing Recount Text, Participation, Picture Series